2014
DOI: 10.1001/jamainternmed.2013.14673
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-2 Receptor Antagonists vs Proton Pump Inhibitors on Gastrointestinal Tract Hemorrhage and Infectious Complications in the Intensive Care Unit

Abstract: IMPORTANCE Histamine-2 receptor antagonists (H 2 RAs) and proton pump inhibitors (PPIs) are commonly used to prevent gastrointestinal tract (GI) hemorrhage in critically ill patients. The stronger acid suppression of PPIs may reduce the rate of bleeding but enhance infectious complications, specifically pneumonia and Clostridium difficile infection (CDI). OBJECTIVE To evaluate the occurrence and risk factors for GI hemorrhage, pneumonia, and CDI in critically ill patients. DESIGN, SETTING, AND PARTICIPANTS A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
184
2
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(212 citation statements)
references
References 40 publications
9
184
2
11
Order By: Relevance
“…The potential adverse effect of PPI use is the increased incidence of pneumonia and Chlostridium difficilis infection (Maclaren et al, 2014). Given the overall uncertain balance between benefit and arm, some author suggest not to routinely use PPIs (Krag et al, 2016).…”
Section: Stress Gastric Ulcers In Cancer Patientsmentioning
confidence: 99%
“…The potential adverse effect of PPI use is the increased incidence of pneumonia and Chlostridium difficilis infection (Maclaren et al, 2014). Given the overall uncertain balance between benefit and arm, some author suggest not to routinely use PPIs (Krag et al, 2016).…”
Section: Stress Gastric Ulcers In Cancer Patientsmentioning
confidence: 99%
“…Other recent research shows a growing use of PPIs as the primary SUP agent, ranging from 39-70%. 6,9,10,12 This may reflect perceived superiority of PPIs as indicated in a recent systematic review and meta-analysis. The study at issue showed that PPIs were associated with a 60% relative risk reduction in clinically important stress ulcer-related GI bleeding when compared with H2RAs.…”
Section: Discussionmentioning
confidence: 99%
“…Their study results showed that 62% of patients received PPIs and 38% received H2RAs. 9 In a recent international survey, PPIs were identified as the most common agent (66%) for SUP. 10 Despite their widespread use, questions are emerging about whether SUP is still indicated.…”
Section: Résumémentioning
confidence: 99%
“…The stronger acid suppression of PPIs enhances the risk of infections. This feature is less expressed in H₂RA activity, and also limits the reperfusion injury in animal models, possibly by reducing oxidative stress after mucosal injury [20]. To see if PPIs administration is a risk factor for infection we use a logistic regression model.…”
Section: Discussionmentioning
confidence: 99%